KONTRIBUSI PENGETAHUAN IBU TERHADAP STATUS IMUNISASI ANAK DI TUJUH PROVINSI DI INDONESIA - Ayubi, Dian (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2009)
Background: Knowledge of mothers is an important variable that affects the mothers to immunize their children. This study aimed to know association of mothers knowledge with immunization status of child under two years age after controlling others confounding variables (education background, economic status, cost, and distance).Method: Study design used cross-sectional cluster survey design of primary data. Data were collected in seven provinces which covered 27 districts. Sample was households who had youngest children aged under two years, total sample was 1149 households. Immunization status was measured by mother’s memorazation and/or health card.Results: This study found 44.3% children received completely immunization. Those 91% of mothers have lack of knowledge about immunization, however, 51.2% of them know benefit of immunization. Children who have mothers with good knowledge will receive immunization completely 2.21 times compared to children who have mother whith poor of knowledge after controlling mother’s education background.